A novel one-step hydrothermal method to prepare CoFe2O4/graphene-like carbons magnetic separable adsorbent. (August 2016) - Dong, Na; He, Fangzhen; Xin, Junlian; Wang, Qizhao; Lei, Ziqiang; Su, Bitao
Graphical abstract: Highlights: A novel one-step hydrothermal method was developed to prepare CoFe2 O4 /LGC. The synthesis is of green non-pollution, simpleness, speediness and low cost. The composite material has good adsorptive property for MB. CoFe2 O4 /LGC could be easily separated by an external magnet and repeatedly used. Abstract: In this study, a novel one-step hydrothermal method was developed and composite material of CoFe2 O4 /graphene-like carbons (LGC) was successfully prepared from pomelo peels (PP), Fe(NO3 )3 ·9H2 O and Co(NO3 )2 ·6H2 O. The characterizing results demonstrate that during the hydrothermal process, (Fe 3+ + Co 2+ ) ions adsorbed on the active surface of PP and PP catalyze/prompt the conversions of PP to LGC and (Fe 3+ + Co 2+ ) to CoFe2 O4, respectively, to produce the composite CoFe2 O4 /LGC. And CoFe2 O4 /LGC is nanosized and made of multilayer nanosheets. Its improved adsorptive property for methylene blue (MB) in water is ascribed to the conversion of PP to LGC and exfoliation of PP sheets to nanosheets. Additionally, the composite can be easily and rapidly separated under an external magnetic field and repeatedly used. MB adsorption on CoFe2 O4 /LGC follows pseudo-second-order kinetics model and Langmuir isotherm models. The synthesis is of simpleness, speediness, low cost, and green non-pollution. CoFe2 O4 /LGC is an ideal adsorbent candidate.